Phycoremediation using botryococcus sp. as nutrients removal in organic wastewaters coupled with hydrocarbon production - Gani, Paran (2017)
Rapid population growth and industrial development are expected to contribute extremely to the world environmental crisis due to the excessive wastewater generation, global warming, climate change and increased use of petroleum fuels. In response to the problems, new technology via phycoremediation to reduce the wastewater contamination coupled with production of sustainable hydrocarbon has received much interest worldwide. Thus, the aim of the study is to produce the hydrocarbon from microalgae, Botryococcus sp. combined with phycoremediation of domestic wastewater (DW) and food processing wastewater (FW). The Botryococcus sp. locally isolated from the tropical rainforest. The optimisation study proved that the Botryococcus sp. grew well in the temperature of 23-33°C, the light intensity of 243 μmol m-2s-1 and 24 hours of light exposure. In fact, this Botryococcus sp. much more tolerated with the outdoor condition when integrated with wastewater phycoremediation in term of biomass productivity and wastewaters bioremediation. The best microalgae concentration was performed at 106 cells/mL for both wastewaters. The highest removal of nutrients (TP, TN and TOC) in DW and FW up to 100% and 92.8%, respectively under outdoor condition; while 95.4% and 76.4%, respectively under indoor condition. Selected heavy metal (Zn, Fe, Cd, Mn) study showed a very significant reduction (p<0.05) for both wastewaters as influenced by culture conditions. In flocculation harvesting, alum indicated the best coagulant to recover microalgae biomass from DW with efficiency up to 99.3% while chitosan showed a good candidate to harvest Botryococcus sp. from FW with efficiency about 94.9%. This study notably found that different culture media used in cultivation produced difference kinds of hydrocarbon compounds. As known, the biggest contribution of this algae oil as biofuel feedstock that potentially contributes to the development of renewable energy technology. Moreover, the hydrocarbon compounds obtained also have bright perspective to be used as a chemical value added in any related industry.